Dr. Jonathan Ng: Where It All Began - Chan, Madeline; Sun, Jeffrey (The Meducator, 2022)
As a celebration of our 20th anniversary, we introduce you to Dr. Jonathan Ng, founder of The Meducator. As a Health Sciences student in 2002, Dr. Ng started The Meducator in hopes of giving undergraduate students the opportunity to be involved in academia. Two decades later, we bring Dr. Ng back to discuss his original visions for The Meducator, how it compares to where we are now, and how we hope The Meducator will continue to grow in the next 20 years. Dr. Ng is currently a family physician who provides primary healthcare to the Ottawa community. Let this interview be an opportunity for us to reconnect with our roots.